Fructo-oligosaccharides purification from a fermentative broth using an activated charcoal column - Nobre, Clarisse (2012)
In this study, a simple and efficient process to purify fructo-oligosaccharides (FOS) from a fermentative broth was proposed using a single activated charcoal column. The FOS adsorption onto the activated charcoal was modeled by a pseudo-second order model. Several volumes and concentrations of water/ ethanol were studied to optimize the selective desorption of sugars from the broth mixture at 25 8C. Mixtures containing 50.6% (w/w) of FOS (FOS content in the fermentative broth) were purified to 92.9% (w/w) with a FOS recovery of 74.5% (w/w). Moreover, with the proposed process, fractions with purity up to 97% (w/w) of FOS were obtained. This purification process was also found to be efficient in the desalting of the fermentative broth.